Transformación digital y su relación con el desempeño de los funcionarios del gobierno autónomo descentralizado provincial de los ríos (zona norte), 2024 - Cantos Salazar , Jazmín Paola (2025)
This research was conducted within the Decentralized Autonomous Government of Los Ríos (Northern Zone), the entity responsible for formulating and implementing plans, programs, and projects that promote the province's social, economic, and productive development. The objective was to evaluate the influence of digital transformation on the performance of this agency's officials, particularly in the northern part of the province. The research focused on the digital strategies implemented within the Decentralized Autonomous Government of Los Ríos (Northern Zone), digital culture, the causes of digital transformation, and the level of knowledge about digital tools and their impact on process efficiency and the achievement of institutional goals. A descriptive and explanatory methodology was used, with a mixed quantitative-qualitative approach, based on correlational quantitative, phenomenological qualitative, inductive, deductive, and analytical methods. Likert-scale surveys and semi-structured interviews were conducted with departmental officials, leaders, or coordinators, and with the Human Resources Manager of the Los Ríos Provincial Autonomous Government (GAD) (North Zone). Information was collected on the adoption and use of digital technologies to understand the causes and challenges faced by officials in implementing digital tools. This research was relevant due to the growing need for public administration to adapt to technological demands, seeking a more efficient and transparent government. The results helped identify areas for improvement in the digital transformation process within the Los Ríos Provincial Autonomous Government (GAD) (North Zone), and recommendations were made to optimize institutional performance, contributing to better public service and the development of the province.